Foreign Body Ingestion in Children: An Experience of 99 Cases in a Tertiary Care Center in Delhi - Meghna Kinjalk; Mehak Sehgal; Simmi K. Ratan; Nitin Jain; Chiranjiv Kumar Gupta; Sujoy Neogi; Prafull Kumar; Dhruv Bhoria; Vanshika Arora; Gautam Chellani (Wolters Kluwer Medknow Publications, 2024)
Background: Accidental ingestion of foreign bodies in children is critical, as the inability to effectively communicate can potentially lead to devastating consequences. We aimed to determine the epidemiology of foreign body ingestion and variability according to age, gender, type, and location of foreign body, and describe its management. Aim and Objective: The aim was to study the various types of foreign body ingestions in children admitted to pediatric surgery and their management. Materials and Methods: A retrospective study was conducted from January 2020 to June 2022 on children under the age of 12 years with a confirmed diagnosis of foreign body ingestion. Patients were clinically and radiologically assessed, after which standard protocols were followed wherein patients were followed by either observation or emergent management. Emergent management included removal of the foreign body by either endoscopy or surgery. Comparisons among multiple age groups, gender, type of foreign body, location of foreign body, and their management were analyzed. Results: Out of 99 subjects in our study, there were 76 boys and 23 girls. The median age of presentation was 5 years. Most children were asymptomatic at presentation. The most frequently ingested foreign body was a coin in all age groups. The majority of the foreign bodies were suspected to be in the small bowel. The foreign bodies that had crossed the duodenojejunal flexure (n = 74, 74.7%) were managed conservatively with the observation of a variable period of a minimum of 24 h and a maximum of 48 h. 21 cases were managed by endoscopic removal, while three cases required surgical intervention. Conclusions: Overall, the most common gastrointestinal foreign body was a coin in all age groups. Button battery is the most worrisome foreign body; however, depending on its position, it can be managed conservatively. Upper GI foreign bodies can be safely removed endoscopically. Parental counseling is very important for the prevention of ingestion of foreign bodies.